Alpha-fetoprotein upregulates hepatocellular carcinoma cell-intrinsic PD-1 expression through the LATS2/YAP/TEAD1 pathway - Leng, Guangxian; Gong, Hongxia; Liu, Guiyuan; Kong, Yin; Guo, Liuqing; Zhang, Youcheng (Biochimica et biophysica acta. General subjects, 2024)
Hepatocellular carcinoma (HCC) cell-intrinsic programmed death 1 (PD-1) promotes tumor progression. However, the mechanisms that regulate its expression are unclear. This study investigated the impact of alpha-fetoprotein (AFP) on HCC cell-intrinsic PD-1 expression. The expression of PD-1 and AFP at the gene and protein levels was detected using real-time fluorescence quantitative polymerase chain reaction (RT-qPCR) and western blotting (WB). Proteins interacting with AFP were examined by co-immunoprecipitation (CO-IP). Chromatin immunoprecipitation (ChIP) and dual luciferase reporter assays were used to identify transcription-enhanced association domain 1 (TEAD1) binding to the promoter of PD-1. The expression of HCC cell-intrinsic PD-1 was positively correlated with AFP. Mechanistically, AFP inhibited the phosphorylation of large tumor suppressor 2 (LATS2) and yes-associated protein (YAP). As a result, YAP is transferred to the nucleus and forms a transcriptional complex with TEAD1, promoting PD-1 transcription by binding to its promoter. AFP is an upstream regulator of the HCC cell-intrinsic PD-1 and increases PD-1 expression via the LATS2/YAP/TEAD1 axis. Our findings provide insight into the mechanisms of HCC development and offer new ideas for further in-depth studies of HCC. •Hepatocellular carcinoma (HCC) cells express programmed death protein 1 (PD-1).•HCC cell-intrinsic PD-1 expression is associated with alpha-fetoprotein (AFP).•The YAP/TEAD1 complex promotes HCC cell-intrinsic PD-1 transcription.•AFP enhances the transcriptional function of the YAP/TEAD1 complex via LATS2/YAP.•AFP upregulates HCC cell-intrinsic PD-1 transcription via the LATS2/YAP/TEAD1 axis.